Expanding the aplicability of secant method with applications - Magreñán, Á. Alberto; Argyros, Ioannis K (Bulletin of the Korean Mathematical Society, 2017)
We present new sufficient convergence criteria for the convergence of the secant-method to a locally unique solution of a nonlinear equation in a Banach space. Our idea uses Lipschitz and center Lipschitz instead of just Lipschitz conditions in the convergence analysis. The new convergence criteria can always be weaker than the corresponding ones in earlier studies. Numerical examples are also provided in this study to solve equations in cases not possible before.
Keywords: secant method; banach space; majorizing sequence; divided difference; Frechet derivative; JCR; Scopus